Implementation of School-Based Management and Improving the Quality of Education at SMK Negeri 2, Jambi City - Hendri, Hendri; Mukminin, Amirul; Sofyan, Sofyan; Fridiyanto, Fridiyanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This research aims to analyze the implementation of school-based management at SMK Negeri 2 Jambi City. This type of research is qualitative research with a case study approach. This research uses interviews and documents to collect data. There were seven participants in this research, including the principal, school committee, deputy principal for curriculum, deputy principal for student affairs, school treasurer, two teachers, and students. The results of this research are that the appointment of School Based Management at SMK Negeri 2 Jambi City has been carried out well. First, starting from planning, namely student affairs arrangements from student registration to various activities that can be carried out in the student affairs department. Furthermore, curriculum management and school teaching programs are given the freedom to develop the curriculum. Furthermore, financial management and financing can be seen from the orderly determination of the school budget, the existence of financial transparency. Second, the implementation of SBM for educational staff at SMK Negeri 2 Jambi City is good because they have expertise in their respective fields. Facilities and infrastructure management can be seen from the school's efforts to provide facilities and infrastructure, maintenance and development so that it can help the teaching and learning process run smoothly. Third, the financial planning evaluation is conveyed to the school community and the school committee by holding a parent meeting. Reporting on program implementation and finances is done by making reports